Preparation and in Vitro Evaluation for Different Types of Ondansetron Hydrochloride Transdermal Patches - Karima Abd allatif; Jameela Ali Hasian (College of Pharmacy University of Baghdad, 2023)
This research aims to develop transdermal patches of Ondansetron hydrochloride (OSH) with different types of polymers, ethyl cellulose and, polyvinyl pyrrolidone k30 in a ratio (3:0.5,3:1,3:2,2:1,1:1) with propylene glycol 20%w/w as a plasticizer. Prepared transdermal patches were evaluated for physical properties. The compatibility between the drug and excipients was studied by Differential scanning calorimetry (DSC), where there is no interaction between the drug and polymers. From the statistical study, there is a statistical difference between all the prepared formulations p<0.05. In-vitro Release study of transdermal patches was performed by using a paddle over the disc. The release profile of OSH followed Korsmeyer - Peppas Model in P2, P4 formulations and, Higuchi Model in P1, P3, P5 formulations. The best formulation P6 carrying EC:PVP in ratio1:1 released 96.47% of ondansetron hydrochloride during 12 h. The release profile of P6 followed the Higuchi model and correlation coefficient  (r2 = 0.9815)